Selective Antibiotic Treatment for Dairy Cow Mastitis - Kathryn Merriman; Fiona Maunsell; Corwin Nelson; Albert De Vries (EDIS)
Mastitis is the most common disease in dairy cattle and is estimated to cost dairy farmers $179 a case. When farmers detect clinical mastitis, they usually take immediate action with antibiotics; but many cases either do not need antimicrobial treatment, resolve without treatment, or are not effectively treated by the antimicrobial used. A selective treatment approach can be more effective. This two-step strategy involves first identifying the pathogen, then deciding on a treatment — this would decrease the use of antimicrobials as well as treatment-associated costs for the farmer. This 5-page fact sheet was written by Kathryn Merriman, Fiona Maunsell, Corwin Nelson, and Albert De Vries, and published by the UF Department of Animal Sciences, December 2014. (Photo: University of Minnesota Laboratory for Udder Health, 2004)